A CONTRASTIVE RHETORICAL ANALYSIS OF PHILIPPINE AND SRI LANKAN ENGLISH NEWS COMMENTARIES - Mabuan, Romualdo Atibagos (Universitas Pendidikan Indonesia, 2017)
Newspaper commentaries constitute a part of media discourse, which is a significant area of inquiry in intercultural rhetoric analysis. Through conducting a contrastive textual analysis of newspaper commentaries culled from the English newspapers in the Philippines and Sri Lanka, this paper explored the notions of genre and micro-genre on the 2015 papal visit in the two countries. To set a tertium comparationisin examining the genre-newspaper commentaries on the papal visit, the timeframe was set during the two-week duration of the visit. To investigate the micro-genres employed by the writers, two sets of 15 newspaper commentaries on the visit respectively in the Philippines and Sri Lanka were selected and analyzed. Findings revealed that both Filipino and Sinhalese writers in English newspaper commentaries tended to employ the micro-genre of â€œmedia explanatory expositionâ€ more often than other micro-genres, and in terms of rhetorical structures, both of these writers tended to show variation, dynamism, and individuality. Implications for ESL (English as a second language) and EFL (English as a foreign language) teaching are provided in the light of these findings.Â